1997
DOI: 10.1128/jvi.71.11.8330-8339.1997
|View full text |Cite
|
Sign up to set email alerts
|

Functional involvement of polypyrimidine tract-binding protein in translation initiation complexes with the internal ribosome entry site of foot-and-mouth disease virus

Abstract: The synthesis of picornavirus polyproteins is initiated cap independently far downstream from the 5 end of the viral RNA at the internal ribosome entry site (IRES). The cellular polypyrimidine tract-binding protein (PTB) binds to the IRES of foot-and-mouth disease virus (FMDV). In this study, we demonstrate that PTB is a component of 48S and 80S ribosomal initiation complexes formed with FMDV IRES RNA. The incorporation of PTB into these initiation complexes is dependent on the entry of the IRES RNA, since PTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 49 publications
(82 reference statements)
5
58
0
Order By: Relevance
“…Several mammalian pyrimidine‐binding proteins have been implicated so far in translational control: (a) polypyrimidine tract binding protein (PTB), which has been implicated in the regulation of translation initiation of picornavirus mRNAs [108,109]; (b) heterogeneous nuclear ribonucleoprotein K (hnRNP K), which selectively and strongly binds poly(C) homopolymer [110] (this protein has recently been shown to operate during erythroid differentiation, together with hnRNP E1, as a translational silencer of 15‐lipoxygenase mRNA [111]); (c) hnRNP E1 (also known as PCBP 1 or αCP1); and (d) hnRNP E2 (PCBP‐2, αCP2). The latter two proteins are closely related exhibiting an overall structural identity of about 85%, and displaying a high affinity for poly(rC) relative to other homoribopolymers [112].…”
Section: Candidate Trans‐acting Factorsmentioning
confidence: 99%
“…Several mammalian pyrimidine‐binding proteins have been implicated so far in translational control: (a) polypyrimidine tract binding protein (PTB), which has been implicated in the regulation of translation initiation of picornavirus mRNAs [108,109]; (b) heterogeneous nuclear ribonucleoprotein K (hnRNP K), which selectively and strongly binds poly(C) homopolymer [110] (this protein has recently been shown to operate during erythroid differentiation, together with hnRNP E1, as a translational silencer of 15‐lipoxygenase mRNA [111]); (c) hnRNP E1 (also known as PCBP 1 or αCP1); and (d) hnRNP E2 (PCBP‐2, αCP2). The latter two proteins are closely related exhibiting an overall structural identity of about 85%, and displaying a high affinity for poly(rC) relative to other homoribopolymers [112].…”
Section: Candidate Trans‐acting Factorsmentioning
confidence: 99%
“…Studies of picornaviruses revealed that PTB plays a role in internal ribosome entry site (IRES)-mediated translation by mechanisms distinct from those governing the cap-dependent translation of most eukaryotic mRNAs . PTB was found to be associated with the IRES elements of encephalomyocarditis virus and foot-and-mouth-disease virus and to stimulate translation ini-tiated from these IRES elements Niepmann 1996;Niepmann et al 1997).…”
Section: Ptbmentioning
confidence: 99%
“…In addition, picornaviruses recruit unconventional cellular proteins, e.g., the 57-kDa polypyrimidine tract-binding protein (PTB). PTB binds to several IRES elements and enhances translation of foot-andmouth disease virus (FMDV) (13,14), and EMCV (2,5).…”
mentioning
confidence: 99%